Evaluation Analysis of Educational Programs - Aulya, Annisa Fitri; Suparman, Nurjamiah; Kaunain, Safitri Nuril (Journal of Quality Assurance in Islamic Education (JQAIE), 2022)
This study aims to understand more deeply about the concept of evaluating educational programs by reviewing the article that has been made before. The method used in this study is qualitative with the type of literature review research or literature review. Literature research or literature review is research that examines or critically reviews the knowledge, ideas, or findings contained in the academic literature. The data source is searched through google scholar using the keyword 'educational program'. The nature of this study is descriptive analysis, which is the regular decomposition of the data that has been obtained. The results of this study, namely the evaluation of educational programs, will have a positive impact on the development of educational programs. Evaluation of educational programs is very important to provide recommendations as a consideration in determining decisions on programs that have been implemented. Evaluation of educational programs can determine the right decision according to the results of the evaluation. The evaluation will also measure the achievement of each program that has been implemented in accordance with the desired objectives.